Effect of orchidectomized and exogenous administration of testosterone on the quantification of platelets in male wistar rats: Efecto de la orquidectomización y la administración exógena de la testosterona en la cuantificación de las plaquetas en ratas wistar macho - Fuentes Vargas, Milagros A. (2021)
Introduction: Anabolic-androgenic steroids (AAS) modify the physiological functioning of the cardiovascular system and have possible effects on the origin of cardiovascular thrombosis. Objective: To determine the impact of the testosterone metabolite on platelet quantification in ORX rats with or without DHT replacement. Material and methods: 24 male 45-day-old Wistar rats underwent orchidectomy with a simple scrotal incision. At 2.5 months of age, the 24 rats were divided into 4 study groups. Half of the 12 male ORX rats received hormone replacement with dihydrotestosterone propionate (DHT) at a 2 mg/kg dose via subcutaneous injection for 7 days and the other half received a physiological solution (0.9% NaCl). The same occurred in the 12 non-ORX males (SHAM). After 7 days of the administration, blood was collected by orbital puncture, and platelet quantification was performed. Results: A significant difference (ANOVA, p < 0.005) was found between the 4 groups. When performing the Dunn Method, a significant difference (p < 0.05) was found in the endogenous administration of DHT between Sham rats and rats ORX + 0.9% NaCl but not with ORX + DHT. Conclusions: DHT induces an increase in platelet quantification inrats Sham and not in ORX rats with DHT, which may affect the increase in platelet quantification.